'Visual Snow' - Distinct from Migraine Aura - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from University of California, San Francisco; King's College London, UK; and University of Utah, Salt Lake City, studied patients with 'visual snow' to characterize the phenotype and compare it to migraine aura.